Is The New Fundeb a Victory? An analysis of the political disputes over the New Fundeb’s Project - Gluz, Micaela Passerino (2021)
This paper analyzes the procedure for the Constitutional Amendment Proposal (PEC) No. 15/2015 of the Chamber of Deputies and No. 26/2020 of the Federal Senate. As a specific objective, we seek to analyze the dynamics of the congressional dispute over the proposal for the new Fund for the Maintenance and Development of Basic Education and the Valorization of Education Professionals (Fundeb), based on positions regarding the financial complementation of the Union. The method of documentary research with a qualitative approach was used. The sources chosen are documents produced by the Special Commission of PEC No. 15/2015 and PEC No. 26/2020 and by social institutions, in particular, Campanha Nacional pelo Direito à Educação and from Todos Pela Educação. It was possible to identify that there were advances, such as the constitutionalization of both Fundeb and the Student-Quality Cost (CAQ), however the political project of New Fundeb is far from being ideal for the Brazilian population.